(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
According to a World Health Organization report, tuberculosis (tuberculosis) is the most deadly disease on the planet. It is noted that global efforts have saved 54 million people from dying from tuberculosis since 2000, but 1.6 million people died from it in 2017 alone.